2009
DOI: 10.1177/1049731508329394
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Observational Pain Scales in Nonverbal Elderly With Cognitive Impairments

Abstract: Objective: Pain assessment for nonverbal older adults with cognitive impairments or dementia presents many challenges, and it is important to determine which scales are most useful in assessing pain among this population. Method: In this review 11 observational scales for assessment of pain in older adults with dementia or cognitive impairments are evaluated in four areas: pain indicators, reliability, validity, and clinical utility of the measure. Results: Results indicate that various scales are available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 63 publications
(117 reference statements)
0
13
0
Order By: Relevance
“…However, in general, the reporting lacked detail. For example, as shown in Tables 4 and 5, the list of included/excluded studies was provided in only three reviews, 67,86,87 the explicit involvement of two or more independent reviewers (question 2) was reported in only one review, 86 only three reviews 67,82,86 explained the methods used to combine findings (question 9) and only one review 86 seemed to have assessed the likelihood of publication bias. This lack of detail in reporting may be because of restrictions on word limits in publications.…”
Section: Description Of Included Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in general, the reporting lacked detail. For example, as shown in Tables 4 and 5, the list of included/excluded studies was provided in only three reviews, 67,86,87 the explicit involvement of two or more independent reviewers (question 2) was reported in only one review, 86 only three reviews 67,82,86 explained the methods used to combine findings (question 9) and only one review 86 seemed to have assessed the likelihood of publication bias. This lack of detail in reporting may be because of restrictions on word limits in publications.…”
Section: Description Of Included Reviewsmentioning
confidence: 99%
“…Three reviews 82,86,87 also explicitly aimed at an evaluation of the evidence, that is to critically evaluate the existing tools, or to identify key components and analyse the reported psychometric properties of tools. Two reviews 64,82 reported a systematic method for evaluation of the tools.…”
Section: Description Of Included Reviewsmentioning
confidence: 99%
See 3 more Smart Citations